Development of Y-chromosome-Specific SCAR Markers Conserved in Taurine, Zebu and Bubaline Cattle - Alves, B. C. A.; Hossepian de Lima, V. F. M. [UNESP]; Moreira-Filho, C. A. (Wiley-Blackwell Publishing, Inc, 2010)
ContentsSex pre-selection of bovine offsprings has commercial relevance for cattle breeders and several methods have been used for embryo sex determination. Polymerase chain reaction (PCR) has proven to be a reliable procedure for accomplishing embryo sexing. To date, most of the PCR-specific primers are derived from the few single-copy Y-chromosome-specific gene sequences already identified in bovines. Their detection demands higher amounts of embryonic genomic material or a nested amplification reaction. In order to circumvent this, limitation we searched for new male-specific sequences potentially useful in embryo sexing using random amplified polymorphic DNA (RAPD) analysis. Random amplified polymorphic DNA (RAPD) assay reproducibility problems can be overcome by its conversion into Sequence Characterized Amplified Region (SCAR) markers. In this work, we describe the identification of two bovine male-specific markers (OPC16(323) and OPF10(1168)) by means of RAPD. These markers were successfully converted into SCARs (OPC16(726) and OPF10(984)) using two pairs of specific primers.Furthermore, inverse PCR (iPCR) methodology was successfully applied to elongate OPC16(323) marker in 159% (from 323 to 837 bp). Both markers are shown to be highly conserved (similarity >= 95%) among bovine zebu and taurine cattle; OPC16(323) is also highly similar to a bubaline Y-chromosome-specific sequence. The primers derived from the two Y-chromosome-specific conserved sequences described in this article showed 100% accuracy when used for identifying male and female bovine genomic DNA, thereby proving their potential usefulness for bovine embryo sexing.